Sosialisasi Kesadaran Keamanan Siber dan Perlindungan Data Pribadi Bagi Warga di Kelurahan Pangkalan Jati, Kota Depok - M. Prakoso Aji; Subakdi Subakdi (Jurnal Syntax Admiration, 2024)
This community service activity (PKM) was held to organize socialization of cybersecurity awareness and personal data protection. Through this socialization activity, it is hoped that it can help the community in dealing with actual situations and conditions related to cyber threats and data leaks that are currently rampant. This Community Service Activity is aimed at residents of Pangkalan Jati Village, Depok City. This activity aims to provide socialization and understanding of the importance of cybersecurity awareness and personal data protection for all levels of society. Supported by a good situation and conditions, this activity was held face-to-face directly at the Pangkalan Jati Village Hall. The number of participants who attended was around 30 people consisting of community leaders, RT Heads, and the younger generation in the Pangkalan Jati Village area, Depok City. This socialization explained material regarding the urgency of cybersecurity awareness, various regulations and policies related to cyber and personal data protection, to various tips for protecting each person's personal data. Moreover, in the context of the 2024 election which has just been implemented, it can be a challenge in itself with the massive developments in cyberspace. Through this activity, it can be concluded that this activity is important to be held routinely because there are still many people who do not understand the urgency of cyber security.